TG: HDL-C Ratio as Insulin Resistance Marker for Metabolic Syndrome in Children With Obesity - Nur Zati Iwani, Ahmad Kamil; Jalaludin, Muhammad Yazid; Yahya, Abqariyah; Mansor, Fazliana; Md Zain, Fuziah; Hong, Janet Yeow Hua; Wan Mohd Zin, Ruziana Mona; Mokhtar, Abdul Halim (Frontiers in Endocrinology, 2022)
Insulin resistance (IR) is an important variable in the diagnosis of metabolic syndrome (MetS). However, the existing pediatric definition of MetS only measures elevated fasting blood glucose (FBG). Arguably, many obese children with severe IR are still able to regulate their FBG well. Hence, this study aimed to assess the utility of triglyceride to high-density lipoprotein (TG: HDL-C) ratio as an IR marker in the modelling of pediatric MetS among children with obesity using structural equation modelling (SEM). A total of 524 blood samples from children with obesity (age 10 to 16 years old) were analyzed for FBG, lipids, insulin, leptin and adiponectin. Both exploratory (EFA) and confirmatory factor analysis (CFA) were used to examine TG: HDL-C ratio as an IR marker in pediatric MetS. EFA shows that TG: HDL-C ratio (standardized factor loading = 0.904) group together with HOMA-IR (standardized factor loading = 0.664), indicating a strong correlation to the IR factor. Replacing FBG with TG: HDL-C ratio improved the modelling of MetS structure in children with obesity. Our MetS model of TG: HDL-C ratio as IR component show comparable model fitness indices (Goodness of Fit, Akaike’s Information Criterion, and Bayes Information Criterion) with leptin: adiponectin ratio (platinum standard for adiposity:IR marker) model. The least model fit was seen when using FBG as an IR surrogate. TG: HDL-C ratio performed better as IR surrogate in MetS structures (standardized factor loading = 0.39) compared to FBG (standardized factor loading = 0.27). TG: HDL-C ratio may be considered as an IR component in pediatric MetS.